Analysis of Strategic Decision of Product Line Extension by IFFCO Using the BCG Model - Asthana, A. K. (Indian Journal of Marketing, 2012)
The Indian Farmer Fertilizer Co-operative Limited (IFFCO) was established in 1967. It started to produce NPK and DAP fertilizers. Then, it added urea fertilizer in its product line. IFFCO is a giant fertilizer company as well as the market leader in production of Urea and Phosphate fertilizers. After capturing 20 percent chemical fertilizer market share, the company decided to extend its product line by diversifying into the insurance and the energy sector. Now, IFFCO is a multi-product, multi-business enterprise. The fertilizer product line of IFFCO needs to be analysed to assess the cash consumption and cash generation position of the product. This analysis will help to determine the continuity of the product in the future and protect its market leader position. Boston Consultancy Group's growth share matrix model, (BCG Model) is an appropriate tools for analysis.